Computational fluid dynamic simulation of abrasive waterjet nozzle erosion - Naqib Hakim, Kamarudin (2020)
The nozzle of the Abrasive Waterjet (AWJ) machine is the most critical component that consequently affects the overall cutting quality, precision, performance and economy. Exposure to slurry of high velocity of water and abrasives makes it susceptible to wear erosion which requires for intermittent reinstatement. Previous simulation of AWJ nozzle erosion have been done by using a 2-D fluid flow model. However, it is important to conduct further simulation using a more accurate 3-D fluid flow model. The present work attempts to simulate the erosion of the nozzle wall using computational fluid dynamics-based software in 3-D. A suitable mesh assembly methods and turbulence model for the simulation of nozzle erosion was identified. Discrete Phase Method (DPM) model was used to simulate multiphase modelling of air, water and abrasives. The Finnie’s erosion and accretion model were selected to find the erosion rate. The erosion profile based on the simulation was compared with the actual profile of worn out nozzle. Furthermore, the nozzle erosion rate for different geometric parameters and working conditions were analyzed based on simulation and experimental results. It was found that the simulations using Quadrilateral and mesh converged well with an error of .645E-08to -1.591E08as compared to Cut-Cell and Tetrahedral mesh which produced some errors between 6.750E-07to -1.231E-08 and 1.868E-08to -6.462E-08, respectively. The Realizable K-ε turbulence model was selected as it shows less error of -3.266E-08to -1.592E-08as compared to Standard turbulence model which between -4.281E-08to -1.290E-08. Furthermore, it was found that the erosion profile with wavy patterns have correlated well past studies using 2-D model Overall, comparing the simulation results under different geometric parameters and operating conditions with empirical models obtained from past studies showed and error in the range of 6.022E-09kg/m2s-1to 1.063E-07 kg/m2s-1. Also, there seems to be consistency in the erosion trend for different simulated parameters with experimental results although the erosion rates appeared to be mostly smaller in values. I can be concluded that the present work has shown an excellent potential for predicting the life of abrasive waterjet nozzle for industrial application.